SIGNIFICANCE OF EXERCISE ( VYAYAMA) IN MODERN ERA - Ahirwar, Harprasad (International Research Journal of Ayurveda & Yoga, 2024)
Exercise is very important to person’s health. Skinny fat person is a tragic base of a human body. It takes the muscles and bone structure not to motion. A healthy mind set to hold yourself strength or confidence. You don’t feel empowered as positive about your body. The answer to this problem is a gift as exercise. As per Ayurveda classics those body movements that produce firmness and strength called vyayama. Basically three different type of exercise namely flexibility, aerobic and anaerobic exercise, wakes upon a different level to maintained the health. Before the commencement of exercise one should follow do and don’ts for exercise described into different classics. In Ayurveda timing for the vyayama is not mentioned clearly but one should have matrapurvakvyayama. The excessive exercise can cause emaciation,thirst , cough, fever etc. So one should perform up to the certain extent that does not causes any harmful impact on the human body. It is best to reduce the obesity, strengthen the muscles, joints and boost the immunity. It provides lightness to the body and maintains the agnibal (the metabolism). It also increase the pulmonary circulation. Promotes vital capacity and facilitate the proper elimination of toxins accumulated in the body. Regular exercise helps in the prevention and treatment of some serious problem like- diabetes mellitus, hypertension and insomnia etc. Scientifically it has proved that some neurochemicals such as endorphin and serotonin are released during exercise which act as pain relieving agent and antidepressant. So exercise described in Ayurveda and modern text have positive impact on overall health of human being.